Karakteristik Pendatang Di Kecamatan Sukajadi Kota Bandung Tahun 2020 - Astri Fadhilah; Muhamad Sopyan Ramdani; Ria Haryatiningsih (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2022)
This study aims to look at the characteristics of migrants in Bandung City in 2020, especially Sukajadi District. From year to year, the number of people migrating to the city of Bandung is increasing, with various reasons that make migrants choose Sukajadi District as a place to seek a better life and seek work experience in the destination city. To achieve this goal, the research was conducted using quantitative methods. The main data used is the 2020 Sukajadi District population report data obtained from the Bandung City Population and Civil Registration Office. Then the data were analyzed descriptively and cross tabulation. The results showed that the existing migrants were categorized into the form of permanent temporal migration. The characteristics of migrants in Sukajadi District are dominated by migrants from the Bandung metropolitan area, very productive age (15-64 years), female, high school education, and private employees.